A configuração do negro escravizado em Úrsula e Assombramento - Neres, Jessica Frizon (2019)
The present work has as object of study the novel Úrsula (1859), by Maria Firmina dos Reis and the novel "Assombramento" by Coelho Netto, works published in the 19th and 20th centuries, respectively. The central purpose of the study is to analyze the configuration of black enslaved from the perspective of each author, observing which features are used to represent the enslavement of the black people. Therefore, the analysis will seek to focus on the characters Túlio and Susana, in the novel of Maria Firmina dos Reis and the trajectory of Ursulina, in the novel of Coelho Netto. In order to support this research, were used authors who dedicate to literary studies, Thomas Skidmore (1976) David Brookshaw (1983), Heloisa Toller Gomes (2009), Marília Conforto (2012), as well as a study on the social imaginary on the question of gender and "race" by Nancy Leys Stepan (1994). Were also indicate out the studies of José Nascimento Morais Filho (1975) and a book organized and commented by Professor Eulálio de Oliveira Leandro (2003) that contemplate the intellectual trajectory of the authors considered in this research. In the chapter of the analysis, the authors used were Eduardo Assis Duarte, Mary Del Priore (2011), David Roas (2014), among others, in the search of the understanding of the present discussions within the works. In addition, it is possible to discuss important points for Brazilian literary studies, the works analyzed offer a perspective on the figure of the black enslaved in an attempt to contribute to the discussions about a past that has been revisited and revised.